Expo Pendidikan: Pemanfaatan Biji Kecipir Sebagai Bahan Alternatif Pembuatan Tempe di Kecamatan So’a - Limbu, Nataniel Umbu; Bao, Antonia P.; Lede, Maria F.H.; Kely, Mario J. (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Old kecipir seeds have no economic value, its thrown away. In actuality, the amino acid makeup of kecipir seeds is nearly identical to that of soybeans, and they contain lipids, proteins, iron, phosphate, vitamin A, magnesium, zinc, and calcium. The protein content of 29% to 38%. Consequently, mature kecipir seeds were processed into tempeh products by Applied Biology program students. The product was on display at a So'a District educational fair. The purpose of this community service project is to educate the local population on how to turn mature kecipir seeds into a valuable tempe product. Training through practice is the approach taken. Panelists, specifically the expo attendees, used organoleptic tests to gather the evaluation of kecipir tempe's quality. Qualitative descriptive methods were used to assess the organoleptic data of product. Because it is thought to be novel in raising the economic value of ancient kecipir seeds from agricultural output, the results demonstrate that kecipir tempe is well-liked by the community. The product looks like kecipir seeds when cut open, yet it still has the same color and scent as ordinary tempeh. When eaten, kecipir tempe has a dense, slightly chewy texture. Tempe kecipir has delicious and looks good.